Muscle activation patterns and patellofemoral pain in cyclists - Dieter, B. P.; McGowan, C. P.; Stoll, S. K.; Vella, C. A. (Medicine & Science in Sports & Exercise, 2014)
Introduction: Patellofemoral pain syndrome (PFPS) is pervasive and debilitating in the sport of cycling. Currently, little is known about the underlying mechanism causing patellofemoral pain in cyclists. Purpose: The purpose of this study was to determine whether temporal differences in the muscle activity of the vastus medialis (VM), vastus lateralis (VL), semitendinosus (ST), and biceps femoris (BF) were correlated to patellofemoral pain in cycling. Methods: Ten healthy cyclists (six women and four men, height = 1.74 ± 0.10 cm, weight = 71.9 ± 16.5 kg, cycling experience = 199.5 ± 82 miles/wk) and seven cyclists with PFPS (one woman and six men, height = 1.84 ± 0.08 cm, weight = 89.8 ± 9.4 kg, cycling experience = 228 ± 51 miles/wk) volunteered to participate in this study. Each participant completed a 10-min cycling trial during which surface EMG was recorded for the VM, VL, ST, and BF muscles. Sagittal plane knee kinematic data were recorded using an electrogoniometer. Results: An ANOVA revealed no significant difference between groups for the differences in onset times of the VM and VL (P = 0.805). There were significant differences between groups for the differences in offset time of the VM and VL (P = 0.032), the differences in onset time of BF and ST (P < 0.001), and the differences in offset time of the ST and BF (P = 0.024). Root mean square values for BF activity were significantly higher in the PFPS group compared with the control (CTL) group (P < 0.01), and ST values were significantly lower in the PFPS group compared with the CTL group (P < 0.01). Root mean square values for BF were significantly greater than ST activity in the PFPS group (P < 0.01) but not in the CTL group (P > 0.05). Conclusion: The results of this study indicate that trained cyclists with PFPS exhibit altered temporal characteristics in muscle activation patterns compared with trained cyclists without PFPS.